Soft budget constraints and regional industrial policy: Reinterpreting the rise and fall of De Lorean - Graham Brownlow (Queen's University Centre for Economic History (QUCEH), 2014)
The rise and fall of De Lorean Motor Cars Limited (DMCL) has been traditionally interpreted as the result either of John De Loreans psychological flaws or as confirming the supposedly inherent weaknesses in activist industrial policy. However, when the episode is examined in more detail, neither of these interpretations is compelling. This papers reinterpretation draws on a range of archival evidence, much of it previously unreleased. The concept of Soft Budget Constraints (SBCs), as pioneered by Kornai, is applied to this evidence. The roles of both government and market failure and the contents of the original contractual agreement are highlighted. The soft budgets promoted by the agreement were in turn traceable to the institutional environment under which industrial policy operated in Northern Ireland. This institutional environment had itself been distorted by the Troubles and the fears policymakers had that a cumulative causation situation existed. Kornais framework helps us piece all the evidence together.
Keywords: N84; N94; O25; 330; soft budget constraints; institutions; industrial policy; violence; Northern Ireland